2009
DOI: 10.3109/00016480903311245
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of sudden low-tone loss other than acute low-tone sensorineural hearing loss

Abstract: The recovery rate at the initial treatment was 47.6% for non-ALHL and 62.9% for ALHL. A Kaplan-Meier plot indicated that cumulative recurrence rates for non-ALHL were 20.2% at 1 year and 43.5% at 5 years, whereas the rates for ALHL were 12.2% at 1 year and 31.3% at 5 years. There was no statistically significant difference between the two patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Increasing evidence suggests that oxidative stress is involved in the development of endolymphatic hydrops and that cellular damage and apoptotic cell death might contribute to the sensorineural hearing loss found in later stages of MD [42]. Oxidation-reduction (redox) based regulation of gene expression appears to be a fundamental regulatory mechanism in cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that oxidative stress is involved in the development of endolymphatic hydrops and that cellular damage and apoptotic cell death might contribute to the sensorineural hearing loss found in later stages of MD [42]. Oxidation-reduction (redox) based regulation of gene expression appears to be a fundamental regulatory mechanism in cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also observed hearing loss recurrence [ 13 ] and percentage of recovery [ 4 ] after differing treatments. Fuse, et al [ 12 ] categorized hearing loss improvements using an audiometric definition, reporting that many ALHL patients achieved complete recovery between 7 and 10 days after administration of steroid.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria for ALHL are not clearly defined, and different studies on ALHL appear to have established their own audiometric definition of ALHL [ 3 4 8 13 14 ]. For our study, we modified the audiometric definition of ALHL proposed by the Study Group for the Acute Profound Deafness Research Committee of the Ministry of Health, Labor and Welfare of Japan [ 3 ], as follows: 1) purely sensorineural hearing impairment with intact tympanic membranes; 2) no history of ocular, vestibular or brain injury; 3) 70 dB or greater sum of pure-tone audiogram hearing loss at three lower frequencies (125, 250, and 500 Hz) and 60 dB or less sum of hearing loss at three higher frequencies (2, 4, and 8 kHz); 4) no history of episodic vertigo or spontaneous nystagmus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, group II patients may be associated with acute low-tone hearing loss without vertigo (ALTHL). The generally used audiometric definition of ALTHL is that the sum of the hearing levels at 125, 250, and 500 Hz should be greater than 70 dB and that the sum of the hearing levels at 2, 4, and 8 kHz, 60 dB or less [ 14 ]. Fushiki et al [ 14 ] reported that the mean age of patients with ALTHL was 37.8 years, which is younger than that of patients with low-tone SSNHL not belonging to the ALTHL group.…”
Section: Discussionmentioning
confidence: 99%